Chitinases genes expression of Beauveria bassiana against Fusarium oxysporum and Peronospora variabilis substrates - Paredes, Maryam (2016)
The Beauveria bassiana filamentous fungus is the most biological control agent frequently used today due to its entomopathogenic activity and antagonist fungi capacity. B. bassiana infects the insects through the degradation of the chitin present in the cuticle, also; affects the cell wall of pathogenic fungi. This mechanism involves enzymatic activities and activation of Chitinase genes. Gene expression of the family 18.4 (XM_008603039.1) and CHIT1 (EU828354.1) of B. bassiana, were evaluated, by RT-qPCR at 0, 4 and 7 days. The assay consists of four media with different carbon sources: colloidal chitin 1.8%, laminarin 0.1%, pulverized of F. oxysporum 0.1% and pulverized leaves infected with P. variabilis 0.1%. Relative expression using actinin and tubulin as referential genes, showed that CHIT1 gene expression increased 1.87 ± 0.35 times on day 7 in the medium with F. oxysporum, while chitinase gene 18.4 family presented the best expression in the medium with P. variabilis increasing 5.88 ± 1.35 times on day 7. This increase in the expression of 18.4 family chitinase genes (XM_008603039.1) and CHIT1 (EU828354.1) of B. bassiana suggests that these enzymes have differential expression in the developing and type of culture.